Accelerated JavaScript training (Packt Publishing, 2018)
"This course will take you on a journey via a hands-on, example-driven JavaScript Bootcamp to guide you through the amazing language of JavaScript. Beginning with the very basics, we walk you through the various characteristics and features JavaScript offers. JavaScript is one of the most important parts of every modern, reactive, user-friendly web page or application."--Resource description page